Given that $\tan(y) =\sinh(x)$ show that $\sin(y) = \pm \tanh(x) $.

I know:




$\tanh\theta = \dfrac{e^x-e^{-x}}{e^x+e^{-x}}$



I'm struggling to link the two together, please assume little to no knowledge of calculus.

  • 3
    $\begingroup$ $\sin\theta = \dfrac{e^{i\theta}-e^{-i\theta}}{2i}$ $\endgroup$ – JohnColtraneisJC Mar 12 '18 at 18:45
  • 4
    $\begingroup$ $\sin i\theta = i \sinh \theta$ $\endgroup$ – JohnColtraneisJC Mar 12 '18 at 18:46
  • $\begingroup$ $${\sinh(i*\Theta)= i*\sin\Theta}$$ $\endgroup$ – ketankk Dec 20 '19 at 6:53

with $$\frac{\sin(y)}{\cos(y)}$$ we get $$\frac{\sin(y)}{\pm\sqrt{1-\sin^2(y)}}=\sinh(x)$$ square this equation and solve the equation for $\sin(y)$ with Algebra we get $$\sin^2(y)=\frac{\sinh^2(x)}{1+\sinh^2(x)}$$ can you finish? after squaring the given equation we obtain $$\frac{\sin^2(y)}{1-\sin^2(y)}=\sinh^2(x)$$ and then $$\sin^2(y)=\sinh^2(x)(1-\sin^2(y))$$ expanding $$\sin^2(y)=\sinh^2(x)-\sinh^2(x)\sin^2(y)$$ this gives $$\sin^2(y)+\sin^2(y)\sinh^2(x)=\sinh^2(x)$$ or $$\sin^2(y)=\frac{\sinh^2(x)}{1+\sinh^2(x)}$$ and note that $$-\sinh^2(x)+\cosh^2(x)=1$$

| cite | improve this answer | |

First of all notice that to keep consistency $$\tanh\theta = \dfrac{e^x-e^{-x}}{e^x+e^{-x}}$$

Should have been $$\tanh(x) = \dfrac{e^x-e^{-x}}{e^x+e^{-x}}$$

Same with your other two functions.

There are many similarities and differences between hyperbolic functions and trig functions.

For example trig functions are periodic but hyperbolic functions are not periodic.

$sin(x)$ and $cos(x)$ are bounded but $sinh(x)$ and $cosh(x)$ are not bounded.

The identities $$ cos^2(x) + sin ^2(x) =1$$

turn into $$ cosh^2(x) - sinh ^2(x) =1$$



turns into


You will learn more about their infinite series and derivatives in your calculus courses.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.